Modified ternary positive electrode material and preparation method thereof
By forming a cobalt-doped porous carbon layer on the surface of the ternary positive electrode material, the structural stability and conductivity problems of the material are solved, and the cycle stability and rate performance of the lithium-ion battery are improved.
Patent Information
- Application Number
- CN202510640345.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-19
- Publication Date
- 2025-09-12
AI Technical Summary
Existing ternary cathode materials have insufficient cycle stability and rate performance at high voltage, their surfaces are easily corroded by electrolytes, and their structural stability and conductivity are poor.
Polyaniline (PANI) was used as a structural regulator. Cobalt-zinc doped polyaniline microspheres were prepared by coprecipitation, mixed with nickel-cobalt-manganese ternary materials and carbonized at high temperature to form a uniform porous carbon layer, which improved the structural stability and conductivity of the material.
It improves the cycle stability and rate performance of the material, inhibits structural collapse during charging and discharging, and improves the lithium ion transmission efficiency and battery energy efficiency.
Smart Images

Figure CN120637419A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion battery positive electrode materials, and in particular to a modified ternary positive electrode material and a preparation method thereof. Background Art
[0002] With the widespread application of lithium-ion batteries in power, consumption and energy storage, the requirements for battery performance are getting higher and higher, especially the requirements for positive electrode materials are becoming more stringent. Ternary positive electrode materials have become one of the most widely used positive electrode materials due to their high gram capacity and excellent rate performance. ix Co y Mn 1-x-y O2(NCM) is considered one of the most important cathode materials for lithium-ion batteries due to its low toxicity, low cost, and high rate capability. However, its surface is easily corroded by the decomposition products of the liquid electrolyte during the electrochemical reaction, severely damaging its surface structure and its inherent low electrical conductivity. As a result, this material suffers from severe capacity decay, poor cycling stability, and disappointing rate performance after long-term cycling at high cutoff voltages.
[0003] To address the above defects, two main material modification methods are used: one is element doping, and the other is surface coating. Element doping mainly involves doping with metal cations or fluoride anions, which can enhance the structural stability of the material to a certain extent. Surface coating technology involves coating the surface of the ternary cathode material with an electrochemically inert protective layer, such as a carbon layer. This can, to a certain extent, inhibit the structural collapse of the material caused by high-voltage charging and discharging, alleviate electrolyte corrosion of the electrode material, and improve the conductivity of the material. However, these two methods have limited effects on improving battery performance, and further research and improvement are still needed. Summary of the Invention
[0004] Based on the technical problems existing in the background technology, the present invention proposes a modified ternary positive electrode material and a preparation method thereof, so that the prepared modified ternary material has excellent rate performance and cycle stability.
[0005] The present invention provides a method for preparing a modified ternary cathode material, comprising the following steps:
[0006] S1. Dissolve a cobalt compound in a solvent and stir under ultrasonic conditions to obtain solution A; dissolve a zinc compound in a solvent and stir under ultrasonic conditions, then add polyaniline and stir under ultrasonic conditions to obtain solution B; in an ice-water bath, add solution A dropwise to solution B, stir to react, and then allow to stand at room temperature, followed by centrifugation, washing, and drying to obtain cobalt-zinc-doped polyaniline microspheres;
[0007] S2. Mix the nickel-cobalt-manganese ternary material with the cobalt-zinc doped polyaniline microspheres, grind them evenly, then heat them to 700-900° C., and calcine them at this temperature for 4-6 hours to obtain the product.
[0008] The present invention uses polyaniline (PANI) as a structural regulator, utilizes the coordination effect of PANI and cobalt-zinc compounds, and coprecipitates to prepare cobalt-zinc-doped polyaniline microspheres; then the cobalt-zinc-doped polyaniline microspheres are mixed with nickel-cobalt-manganese ternary materials, and solid-phase sintering technology is used to carbonize the cobalt-zinc-doped polyaniline microspheres at high temperatures. At the same time, the zinc doped in the microspheres evaporates at high temperatures, so that the microspheres form a porous structure, thereby forming a porous carbon layer uniformly doped with cobalt on the surface of the nickel-cobalt-manganese ternary material to obtain a modified ternary positive electrode material. The above preparation method can eliminate residual lithium on the surface and reduce the pH value of the material as a whole, thereby improving the safety of the battery, improving the cycle performance, and enhancing the charge and discharge efficiency; and the cobalt-doped porous carbon layer formed on the surface of the ternary material can also better improve the structural stability of the material, further inhibit the structural collapse and damage of the electrode material during the charge and discharge process, and effectively improve the cycle stability of the battery; the uniformly distributed pores in the carbon layer are also conducive to the rapid transmission of lithium ions during the charge and discharge process, improving the conductivity of the material, so that the battery has good rate performance and energy efficiency.
[0009] Preferably, in S1, the cobalt compound is at least one of potassium cobalt cyanide, cobalt chloride, and cobalt nitrate; in S1, the zinc compound is at least one of zinc acetate, zinc cyanide, and zinc nitrate; and in S1, the solvent is a mixture of deionized water and N,N-dimethylformamide in a volume ratio of 1:2-3. By selecting appropriate raw materials and solvents, the resulting cobalt-zinc-doped polyaniline microspheres have a more uniform morphology, thereby improving the uniformity of the cobalt-doped porous carbon layer, which is beneficial for further improving the material's charge-discharge efficiency, cycle performance, and rate capability.
[0010] Preferably, the molar ratio of the cobalt compound, zinc compound, and polyaniline is 1:1 to 2:2 to 4. By controlling the molar ratio of the cobalt compound, zinc compound, and polyaniline, the cobalt-doped porous carbon layer formed on the surface of the ternary material has a more optimal structure and composition, thereby further improving the material's charge and discharge efficiency, cycle performance, and rate performance.
[0011] Preferably, the concentration of the cobalt compound in the solution A is 0.01 to 0.1 mol / L.
[0012] Preferably, the concentration of the zinc compound in the solution B is 0.01 to 0.1 mol / L.
[0013] Preferably, in S1, the stirring reaction time is 1 to 2 hours.
[0014] Preferably, the mass ratio of the nickel-cobalt-manganese ternary material to the cobalt-zinc-doped polyaniline microspheres is 0.99-0.999:0.001-0.01. By controlling the mass ratio of the nickel-cobalt-manganese ternary material to the cobalt-zinc-doped polyaniline microspheres, the carbon layer on the surface of the ternary material has an appropriate thickness, thereby further improving the lithium ion transport efficiency and structural stability of the material.
[0015] Preferably, the chemical formula of the nickel-cobalt-manganese ternary material is LiNi x Co y Mn 1-x-y O2, where 0.3≤x≤0.9, 0.1≤y≤0.3. By limiting the chemical formula of the nickel-cobalt-manganese ternary material, it can achieve high energy density, good charge and discharge performance, high safety and good cycle stability.
[0016] The present invention does not particularly limit the preparation method of the nickel-cobalt-manganese ternary material, and conventional methods in the field can be used. Preferably, the preparation method of the nickel-cobalt-manganese ternary material includes: weighing a soluble nickel source, a soluble cobalt source, and a soluble manganese source in a stoichiometric ratio and dissolving them in deionized water to obtain a mixed salt solution; adding the mixed salt solution, sodium carbonate solution, and ammonia water to an ethanol aqueous solution, stirring the reaction, and then filtering, washing, and drying to obtain a nickel-cobalt-manganese ternary precursor; after mixing the nickel-cobalt-manganese ternary precursor with a lithium source, first heating it to 300-500°C at a heating rate of 2-10°C / min, calcining it at this temperature for 4-6 hours, and then heating it to 700-900°C at a heating rate of 2-10°C / min, calcining it at this temperature for 8-12 hours, to obtain the product. The nickel-cobalt-manganese ternary material prepared using the ethanol-water coprecipitation method has regular morphology and uniform particle size. Furthermore, ethanol adsorbs or reacts on the particle surface, improving the material's surface properties, reducing side reactions with the electrolyte, and enhancing the material's interfacial stability. Therefore, the ternary material prepared using the ethanol-water coprecipitation method is beneficial for increasing the material's compaction density and structural stability, further improving the battery's energy density, electron transfer efficiency, and cycle life.
[0017] Preferably, in the preparation method of the nickel-cobalt-manganese ternary material, the soluble nickel source is at least one of nickel chloride, nickel sulfate, and nickel nitrate; the soluble cobalt source is at least one of cobalt chloride, cobalt sulfate, and cobalt nitrate; the soluble manganese source is at least one of manganese chloride, manganese sulfate, and manganese nitrate; the lithium source is at least one of lithium carbonate, lithium hydroxide, and lithium acetate; and the ratio of the total molar amount of nickel, cobalt, and manganese elements in the nickel-cobalt-manganese ternary precursor to the molar amount of lithium element in the lithium source is 1:1 to 1.1.
[0018] Preferably, in the preparation method of the nickel-cobalt-manganese ternary material, the total molar concentration of nickel ions, cobalt ions, and manganese ions in the mixed salt solution is 1-2 mol / L; the concentration of the sodium carbonate solution is 1-2 mol / L; the concentration of the ammonia water is 0.5-1 mol / L; the ethanol aqueous solution is obtained by mixing deionized water and anhydrous ethanol in a volume ratio of 3:2-3; the volume ratio of the mixed salt solution to the sodium carbonate solution, ammonia water, and ethanol aqueous solution is 8-12:2-4:1-3:4-8.
[0019] Preferably, in the method for preparing the nickel-cobalt-manganese ternary material, the stirring reaction temperature is 40-60° C. and the time is 8-12 hours.
[0020] Preferably, in S2, the heating rate is 2-10°C / min. By controlling the appropriate heating rate, the purpose of regulating particle growth, improving particle morphology, optimizing crystal phase purity, and increasing crystallinity can be achieved, thereby further improving material properties and enhancing charge-discharge capacity and cycle stability.
[0021] The present invention also provides a modified ternary positive electrode material, which is prepared by the preparation method.
[0022] The beneficial effects of the present invention are as follows:
[0023] The present invention uses polyaniline (PANI) as a structural regulator, utilizes the coordination effect of PANI and cobalt-zinc compounds, and coprecipitates to prepare cobalt-zinc-doped polyaniline microspheres; then the cobalt-zinc-doped polyaniline microspheres are mixed with nickel-cobalt-manganese ternary materials, and solid-phase sintering technology is used to carbonize the cobalt-zinc-doped polyaniline microspheres at high temperatures. At the same time, the zinc doped in the microspheres evaporates at high temperatures, so that the microspheres form a porous structure, thereby forming a porous carbon layer uniformly doped with cobalt on the surface of the nickel-cobalt-manganese ternary material to obtain a modified ternary positive electrode material. The above preparation method can eliminate residual lithium on the surface and reduce the pH value of the material as a whole, thereby improving the safety of the battery, improving the cycle performance, and enhancing the charge and discharge efficiency; and the cobalt-doped porous carbon layer formed on the surface of the ternary material can also better improve the structural stability of the material, further inhibit the structural collapse and damage of the electrode material during the charge and discharge process, and effectively improve the cycle stability of the battery; the uniformly distributed pores in the carbon layer are also conducive to the rapid transmission of lithium ions during the charge and discharge process, improving the conductivity of the material, so that the battery has good rate performance and energy efficiency. In summary, the modified ternary material prepared by the present invention can significantly improve the rate performance and cycle performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 Schematic diagram of the preparation process of cobalt-zinc-doped polyaniline microspheres in Example 1 of the present invention. DETAILED DESCRIPTION
[0025] The technical solution of the present invention is described in detail below through specific embodiments.
[0026] Example 1
[0027] Example 1 provides a modified ternary cathode material, and the preparation method is as follows:
[0028] S1. Dissolve 4 mmol of potassium cobalt cyanide in 200 mL of solvent and stir under ultrasonic conditions to obtain solution A; dissolve 6 mmol of zinc acetate dihydrate in 200 mL of solvent and stir under ultrasonic conditions, then add 12 mmol of polyaniline and stir under ultrasonic conditions to obtain solution B; in an ice-water bath, add solution A dropwise to solution B, stir and react for 1 hour, then let stand at room temperature for 24 hours, centrifuge, wash the obtained solid with deionized water 6 times, and then dry at 60°C overnight to obtain cobalt-zinc-doped polyaniline microspheres; wherein the solvent is obtained by mixing deionized water and N,N-dimethylformamide in a volume ratio of 1:2;
[0029] S2, 1.998g LiNi 0.8 Co 0.1 Mn 0.1 The O2 nickel-cobalt-manganese ternary material was mixed with 0.002 g of cobalt-zinc-doped polyaniline microspheres, ground evenly, and then placed in a tube furnace. The temperature was raised to 900°C at a heating rate of 5°C / min under a nitrogen atmosphere, kept warm and calcined for 2 hours, and naturally cooled to room temperature to obtain the product.
[0030] Among them, LiNi 0.8 Co 0.1 Mn 0.1 The preparation method of O2 nickel-cobalt-manganese ternary material is as follows:
[0031] Nickel sulfate, cobalt sulfate and manganese sulfate were weighed and dissolved in deionized water in a molar ratio of 8:1:1 to obtain a mixed salt solution, wherein the total molar concentration of nickel ions, cobalt ions and manganese ions in the mixed salt solution was 1 mol / L; the mixed salt solution, a sodium carbonate solution with a concentration of 1 mol / L and ammonia water with a concentration of 0.5 mol / L were added to an ethanol aqueous solution (the ethanol aqueous solution was obtained by mixing deionized water and anhydrous ethanol in a volume ratio of 3:2), stirred at 45°C and a speed of 1200 r / min for 10 hours, then filtered, washed with deionized water 4 times, and heated at 1 The method comprises the following steps: drying at 10°C for 12 hours to obtain a nickel-cobalt-manganese ternary precursor; mixing the nickel-cobalt-manganese ternary precursor with lithium carbonate, heating the mixture to 500°C at a heating rate of 5°C / min, and calcining the mixture under air atmosphere for 5 hours, then heating the mixture to 900°C at a heating rate of 5°C / min, and calcining the mixture under nitrogen atmosphere for 10 hours to obtain a nickel-cobalt-manganese ternary precursor; wherein the volume ratio of the mixed salt solution to the sodium carbonate solution, the ammonia water, and the ethanol aqueous solution is 10:3:2:6, and the ratio of the total molar amount of nickel, cobalt, and manganese elements in the nickel-cobalt-manganese ternary precursor to the molar amount of lithium element in the lithium source is 1:1.05.
[0032] Example 2
[0033] Example 2 provides a modified ternary cathode material, and the preparation method is as follows:
[0034] S1. Dissolve 4 mmol of potassium cobalt cyanide in 200 mL of solvent and stir under ultrasonic conditions to obtain solution A; dissolve 6 mmol of zinc acetate dihydrate in 200 mL of solvent and stir under ultrasonic conditions, then add 12 mmol of polyaniline and stir under ultrasonic conditions to obtain solution B; in an ice-water bath, add solution A dropwise to solution B, stir and react for 1 hour, then let stand at room temperature for 24 hours, centrifuge, wash the obtained solid with deionized water 6 times, and then dry at 60°C overnight to obtain cobalt-zinc-doped polyaniline microspheres; wherein the solvent is obtained by mixing deionized water and N,N-dimethylformamide in a volume ratio of 1:2;
[0035] S2, 1.99g LiNi 0.8 Co 0.1 Mn 0.1 The O2 nickel-cobalt-manganese ternary material was mixed with 0.01 g of cobalt-zinc-doped polyaniline microspheres, ground evenly, and then placed in a tube furnace. The temperature was raised to 900°C at a heating rate of 5°C / min under a nitrogen atmosphere, kept warm and calcined for 2 hours, and naturally cooled to room temperature.
[0036] LiNi 0.8 Co 0.1 Mn 0.1 The preparation method of O2 nickel-cobalt-manganese ternary material is the same as that in Example 1.
[0037] Example 3
[0038] Example 1 provides a modified ternary cathode material, and the preparation method is as follows:
[0039] S1. Dissolve 4 mmol of potassium cobalt cyanide in 200 mL of solvent and stir under ultrasonic conditions to obtain solution A; dissolve 6 mmol of zinc acetate dihydrate in 200 mL of solvent and stir under ultrasonic conditions, then add 12 mmol of polyaniline and stir under ultrasonic conditions to obtain solution B; in an ice-water bath, add solution A dropwise to solution B, stir and react for 1 hour, then let stand at room temperature for 24 hours, centrifuge, wash the obtained solid with deionized water 6 times, and then dry at 60°C overnight to obtain cobalt-zinc-doped polyaniline microspheres; wherein the solvent is obtained by mixing deionized water and N,N-dimethylformamide in a volume ratio of 1:2;
[0040] S2, 1.98g LiNi 0.8 Co 0.1 Mn 0.1 The O2 nickel-cobalt-manganese ternary material was mixed with 0.02 g of cobalt-zinc-doped polyaniline microspheres, ground evenly, and then placed in a tube furnace. The temperature was raised to 900°C at a heating rate of 5°C / min under a nitrogen atmosphere, kept warm and calcined for 2 hours, and naturally cooled to room temperature to obtain the obtained product.
[0041] LiNi 0.8 Co 0.1 Mn 0.1 The preparation method of O2 nickel-cobalt-manganese ternary material is the same as that in Example 1.
[0042] Example 4
[0043] Example 4 provides a modified ternary cathode material, and the preparation method is as follows:
[0044] S1. Dissolve 4 mmol of cobalt chloride in 200 mL of solvent and stir under ultrasonic conditions to obtain solution A; dissolve 4 mmol of zinc acetate dihydrate in 200 mL of solvent and stir under ultrasonic conditions, then add 8 mmol of polyaniline and stir under ultrasonic conditions to obtain solution B; in an ice-water bath, add solution A dropwise to solution B, stir and react for 1.5 hours, then let stand at room temperature for 24 hours, centrifuge, wash the obtained solid with deionized water 6 times, and then dry at 60°C overnight to obtain cobalt-zinc-doped polyaniline microspheres; wherein the solvent is obtained by mixing deionized water and N,N-dimethylformamide in a volume ratio of 1:3;
[0045] S2, 1.99g LiNi 0.8 Co 0.1 Mn 0.1The O2 nickel-cobalt-manganese ternary material was mixed with 0.01 g of cobalt-zinc-doped polyaniline microspheres, ground evenly, and then placed in a tube furnace. The temperature was raised to 700°C at a heating rate of 2°C / min under a nitrogen atmosphere, kept warm and calcined for 6 hours, and naturally cooled to room temperature.
[0046] LiNi 0.8 Co 0.1 Mn 0.1 The preparation method of O2 nickel-cobalt-manganese ternary material is the same as that in Example 1.
[0047] Example 5
[0048] Example 5 provides a modified ternary cathode material, the preparation method of which is as follows:
[0049] S1. Dissolve 4 mmol of cobalt nitrate in 200 mL of solvent and stir under ultrasonic conditions to obtain solution A; dissolve 8 mmol of zinc nitrate in 200 mL of solvent and stir under ultrasonic conditions, then add 16 mmol of polyaniline and stir under ultrasonic conditions to obtain solution B; in an ice-water bath, add solution A dropwise to solution B, stir and react for 2 hours, then let stand at room temperature for 24 hours, centrifuge, wash the obtained solid with deionized water 6 times, and then dry at 60°C overnight to obtain cobalt-zinc-doped polyaniline microspheres; wherein the solvent is obtained by mixing deionized water and N,N-dimethylformamide in a volume ratio of 1:3;
[0050] S2, 1.99g LiNi 0.8 Co 0.1 Mn 0.1 The O2 nickel-cobalt-manganese ternary material was mixed with 0.01 g of cobalt-zinc-doped polyaniline microspheres, ground evenly, and then placed in a tube furnace. The temperature was raised to 800°C at a heating rate of 10°C / min under a nitrogen atmosphere, kept warm and calcined for 4 hours, and naturally cooled to room temperature to obtain the product.
[0051] LiNi 0.8 Co 0.1 Mn 0.1 The preparation method of O2 nickel-cobalt-manganese ternary material is the same as that in Example 1.
[0052] Comparative Example 1
[0053] Comparative Example 1 provides LiNi 0.8 Co 0.1 Mn 0.1 The preparation method of O2 nickel-cobalt-manganese ternary material is the same as that in Example 1.
[0054] Comparative Example 2
[0055] Comparative Example 2 provides a modified ternary positive electrode material, and the preparation method is as follows:
[0056] 1.998g LiNi 0.8 Co 0.1 Mn 0.1 The O2 nickel-cobalt-manganese ternary material is mixed with 0.002 g of polyaniline, ground evenly, and then placed in a tube furnace. The temperature is increased to 900°C at a heating rate of 5°C / min under a nitrogen atmosphere, kept warm and calcined for 2 hours, and naturally cooled to room temperature to obtain the product.
[0057] Comparative Example 3
[0058] Comparative Example 3 provides a modified ternary cathode material, and the preparation method is as follows:
[0059] S1. Mix 4 mmol of potassium cobalt cyanide, 6 mmol of zinc acetate dihydrate, and 12 mmol of polyaniline, and grind them evenly to obtain powder A;
[0060] S2, 1.998g LiNi 0.8 Co 0.1 Mn 0.1 The O2 nickel-cobalt-manganese ternary material is mixed with 0.002 g of powder A, ground evenly, and then placed in a tube furnace. The temperature is raised to 900°C at a heating rate of 5°C / min under a nitrogen atmosphere, kept warm and calcined for 2 hours, and naturally cooled to room temperature to obtain the product.
[0061] Test example
[0062] The materials prepared in the Examples and Comparative Examples were used, respectively, to assemble button cells using a lithium sheet as the counter electrode in an argon-filled glove box. A slurry was prepared with a mass ratio of positive electrode material: SP:PVDF = 96:2:2. The mixture was ground and mixed uniformly, then slurried using NMP as the solvent. The slurry was then evenly coated on aluminum foil, dried under vacuum at 80°C, and compacted at 5 MPa to obtain an electrode sheet. Electrochemical performance was then tested using a Blue Electric test system and an electrochemical workstation at a test voltage of 2.8 to 4.25 V. The results are shown in Table 1.
[0063] Table 1
[0064]
[0065] As shown in Table 1, the modified ternary cathode materials prepared in Examples 1 to 5 of the present invention have greatly improved initial efficiency at a rate of 0.1C, and have a high gram capacity at rates of 0.1C and 1C, indicating that they have good rate performance; at a rate of 1C, after 500 cycles, the capacity retention rate is significantly better than that of the comparative example, wherein the significant improvement in cycle performance may be due to the cobalt-doped porous carbon layer providing a strong support for the NCM ternary material. It can be seen that the modified ternary cathode material of the present invention is used for lithium-ion batteries and has excellent cycle performance and rate performance.
[0066] The above description is only a preferred specific embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any technician familiar with the technical field, within the technical scope disclosed by the present invention, who makes equivalent replacements or changes based on the technical solution and inventive concept of the present invention, should be covered by the scope of protection of the present invention.
Claims
1. A method for preparing a modified ternary cathode material, characterized in that: The following steps are involved: S1. Dissolve a cobalt compound in a solvent and stir under ultrasonic conditions to obtain solution A; dissolve a zinc compound in a solvent and stir under ultrasonic conditions, then add polyaniline and stir under ultrasonic conditions to obtain solution B; in an ice-water bath, add solution A dropwise to solution B, stir to react, and then allow to stand at room temperature, followed by centrifugation, washing, and drying to obtain cobalt-zinc-doped polyaniline microspheres; S2. Mix the nickel-cobalt-manganese ternary material with the cobalt-zinc doped polyaniline microspheres, grind them evenly, then heat them to 700-900° C., and calcine them at this temperature for 2-6 hours to obtain the product.
2. The method for preparing the modified ternary cathode material according to claim 1, wherein: In S1, the cobalt compound is at least one of potassium cobalt cyanide, cobalt chloride, and cobalt nitrate; in S1, the zinc compound is at least one of zinc acetate, zinc cyanide, and zinc nitrate; in S1, the solvent is obtained by mixing deionized water and N,N-dimethylformamide in a volume ratio of 1:2 to 3.
3. The method for preparing the modified ternary cathode material according to claim 1, wherein: In S1, the stirring reaction time is 1 to 2 hours.
4. The method for preparing the modified ternary cathode material according to claim 1, wherein: The molar ratio of the cobalt compound, the zinc compound and the polyaniline is 1:1-2:2-4.
5. The method for preparing the modified ternary cathode material according to claim 1, wherein: The mass ratio of the nickel-cobalt-manganese ternary material to the cobalt-zinc doped polyaniline microspheres is 0.99-0.999:0.001-0.
01.
6. The method for preparing the modified ternary cathode material according to claim 1, wherein: The chemical formula of the nickel-cobalt-manganese ternary material is LiNi x Co y Mn 1-x-y O2, where 0.3≤x≤0.9, 0.1≤y≤0.
3.
7. The method for preparing the modified ternary cathode material according to claim 1, characterized in that: The preparation method of the nickel-cobalt-manganese ternary material includes: weighing a soluble nickel source, a soluble cobalt source, and a soluble manganese source in a stoichiometric ratio and dissolving them in deionized water to obtain a mixed salt solution; adding the mixed salt solution, a sodium carbonate solution, and ammonia water to an ethanol aqueous solution, stirring for reaction, and then filtering, washing, and drying to obtain a nickel-cobalt-manganese ternary precursor; after mixing the nickel-cobalt-manganese ternary precursor with a lithium source, first heating the mixture to 300-500° C. at a heating rate of 2-10° C. / min, calcining the mixture at the temperature for 4-6 hours, and then heating the mixture to 700-900° C. at a heating rate of 2-10° C. / min, and calcining the mixture at the temperature for 8-12 hours to obtain the nickel-cobalt-manganese ternary precursor.
8. The method for preparing the modified ternary cathode material according to claim 1, wherein: In S2, the heating rate is 2 to 10°C / min.
9. A modified ternary cathode material, characterized in that: The invention is prepared by the preparation method according to any one of claims 1 to 8.